External Fixator in Elderly Patients with Hip Fractures - Shrestha, Shilu; Banskota, Bibek; Rajbhandary, Tarun; Shrestha, Babukaji; Pandey, Jwala Raj; Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2013)
Introduction: Fragility fractures around the hip are common in the elderly and are associated with significant morbidity and mortality. Early stabilization and mobilization reduces mortality associated with prolonged recumbence. In patients who are not fi t for general anesthesia, external fixation under local anesthesia will help early mobilization. Methods: A retrospective study of hip fractures treated between 2002 to 2009 was undertaken. Out of 242 hip fractures, 13 patients with inter-trochanteric fractures had undergone external fixator application under local anesthesia. There were 9 females and 4 males; five were on right side and 8 on left side. As per the system of American Society of Anesthesiologists (ASA), 10 were of grade III, 2 of grade IV and 1 of grade E. The age of the patient ranged from 60 to 92 years (average 80 years). The average delay in surgery was 8.2 days for cases presenting soon after the injury. Results: Follow up was done at 6 weeks, 3 months and 6 months with the average follow up of 4.7 months. All the fractures (n=13) united and the average time to radiological union was 3 months. Three patients had grade I pin tract infection which was easily controlled with local care. The average Harris hip score at final follow-up was 92. Conclusion: External fixator can be a valuable tool for the treatment of hip fractures in high risk elderly patients with concomitant medical co-morbidities. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9319 Nepal Orthopedic Association Journal 2013 Vol.3(1): 11-13